1972
DOI: 10.1002/pssa.2210090238
|View full text |Cite
|
Sign up to set email alerts
|

Fast neutron irradiation induced resistivity in metals

Abstract: The residual resistivity increase rate as a function of induced resistivity for fast neutron irradiated Al, Cu, Ag, Au, Pt, Fe, Ni, Co and Mo has been studied. Except for Fe the resistivity increase rate as a function of irradiation induced resistivity is non‐linear. The data is best explained with the expression of Balarin and Hauser. Saturation values of the resistivity and defect concentrations plus static and dynamic recombination volumes have been calculated; they differ from those obtained by irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

1973
1973
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(13 citation statements)
references
References 11 publications
0
9
0
4
Order By: Relevance
“…An analysis of the damage production inelectron-irradiated molybdenum of various purities [7] has, together with the single-crystal results [6], shown the complexity of the atomic displacement process as a result of more than one displacement threshold, again stressing the particular role of focusing collision sequences in the (111) direction. I n relation with this, it is interesting to note the results of Horak and Blewitt [8] who determined the spontaneous recombination volume of a series of neutron-irradiated metals : they found that the only two b.c.c. metals measured, iron and molybdenum, had a remarkably lower recombination volume than the f.c.c.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…An analysis of the damage production inelectron-irradiated molybdenum of various purities [7] has, together with the single-crystal results [6], shown the complexity of the atomic displacement process as a result of more than one displacement threshold, again stressing the particular role of focusing collision sequences in the (111) direction. I n relation with this, it is interesting to note the results of Horak and Blewitt [8] who determined the spontaneous recombination volume of a series of neutron-irradiated metals : they found that the only two b.c.c. metals measured, iron and molybdenum, had a remarkably lower recombination volume than the f.c.c.…”
Section: Introductionmentioning
confidence: 79%
“…In fact, no theory gives us a precise value for this quantity, and very few reliable experimental data exist on the electrical resistivity of a vacancy and/or a n interstitial. From the defect production curves of a series of electron-irradiated metals, Lucasson For molybdenum, this would give 10 to 15 yQcm/atyo; we have chosen the values of 10 pQcm so as to be able to compare the derived values of a, and arO directly with those reported by Horak and Blewitt [8]. For vanadium, the corresponding value was chosen to 40 pQcm/at%.…”
Section: (4)mentioning
confidence: 99%
See 1 more Smart Citation
“…36 ' 37 The excess resistivity at saturation range from 0.34 to 0.33 nSl-cm at ~300 K. This added resistivity represents a 18% increase relative to the electrical resistivity of annealled copper at 300 K.…”
Section: Compression Coilmentioning
confidence: 99%
“…2b). Elles presentent l'allure gBnBrale de celles obtenues lors d'irradiation des metaux purs[9] et des alliages[lo] par des particules Bnergetiques: Blectrons, neutrons, ions; la diminution progressive de la vitesse d'accroissement de Ae pour les fortes fluences caracterise la tendance B la saturation du phenomhne.…”
unclassified